Media GASPOL berbasis wayground: Inovasi game-based learning untuk pemahaman konsep perkalian desimal dan motivasi belajar - Nuraeni Nuraeni; Wahyu Hidayat; Eva Dwi Minarti (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2026)
Conceptual understanding is a fundamental foundation for students. However, in practice, students’ conceptual understanding and learning motivation were still relatively low. This study aimed to develop GASPOL (Game Asyik Perkalian Desimal Online Learning) media based on Wayground. The research employed a Research and Development (R&D) method using the ADDIE model. The subjects consisted of 33 fifth-grade students. The instruments included a conceptual understanding test, a motivation questionnaire, and validation sheets. Data were analyzed using descriptive quantitative methods through percentages and mean scores, the Kolmogorov-Smirnov normality test, Paired Sample T-Test, and N-Gain analysis. The media was implemented using a pair-based collaboration and the Paper Mode feature. The results showed that the GASPOL media was highly feasible based on material expert validation (87.77%) and media expert validation (89.23%). The implementation improved the mean score from 26.00 to 74.25 with an N-Gain of 0.6419 (moderate category). In addition, students’ learning motivation reached 90.73% (very high), and the practicality level was 92,95%. Thus, GASPOL media based on Wayground was effective and feasible as an innovative mathematics learning medium.